Application of the Book Adab Al-'Alim wa Al-Muta'allim to Students' Moral Education - Aulia Ferry Firmasnyah; Mukhamat Saini (STAI Miftahul Ula Nganjuk, 2024)
This study examines the application of the book Adab Al-‘Alim Wa Al-Muta’allim in the moral education of students at MTsN 4 Nganjuk. The book, authored by K.H. Hasyim Asy’ari, provides guidelines on the ethics of learning and teaching, aimed at fostering high moral standards among students. The study employed a qualitative research method, utilizing interviews, observations, and documentation to collect data. Findings indicate that the application of the book's teachings significantly improved students' respect for teachers, time management, and overall ethical behavior. However, challenges such as limited understanding of the Pegon script and varying levels of familial support were identified. Despite these challenges, the successful implementation of the book's principles has led to enhanced moral behavior among students, characterized by increased respect for teachers and peers, as well as a stronger commitment to learning.